Sexually Transmitted Infections: A Novel Screening Strategy for Improving Women’s Health in Vulnerable Populations - Frati, Elena R. (Int J Mol Sci, 2017)
Background: Migrant women are one of the most vulnerable population to health problems and well-being. This study aimed at implementing a counseling and preventive strategy for sexually transmitted infections (STIs) in undocumented migrant women in Milan, Italy. Methods: Women (ages 18–65) were enrolled at the NAGA Centre (2012–2013) and asked for a urine sample in order to carry out molecular detection of Human papillomavirus (HPV), Chlamydia trachomatis (Ct), Trichomonas vaginalis (Tv), Neisseria gonorrhoeae (Ng)-DNA. Socio-demographic and sexual behavior information were collected. All HPV/Ct+ women were offered Pap tests and/or were prescribed antibiotic treatment. Results: 537/757 women participated in the study (acceptability rate: 70.9%). Most of the women were from Latin America (45.6%) and Eastern Europe (30.7%); >60% of them had stable partners, did not use contraception and had had at least one pregnancy. The prevalence rates of HPV, Ct, Tv and Ng infections were 24.2%, 7.8%, 4.8% and 0%, respectively. In all, 43.2% of the positive women agreed to undergo a gynecological examination and accepted suitable treatment. Conclusions: This study shows an overall high prevalence of STIs in undocumented migrant women in Milan. The screening strategy based on counseling and urine testing contributed to the successfully high acceptability rate. More appropriate health services that adequately address all aspects of women’s health are required.